Holistic workplace wellbeing: construct, circumstances and strategic sustainability consequences. (1st April 2019) - Nathan, Maria L.
Wellbeing is defined as peoples' positive evaluation of their lives, including positive emotion, engagement, satisfaction, and meaning (Seligman, 2002). Individual wellbeing results from achievement of physical vitality, mental alacrity, social satisfaction, a sense of accomplishment, and personal fulfilment (Huseyin and Ioannidis, 2015). Workplace wellbeing considers the aspects of overall wellbeing perceived to be determined primarily by work and that can be influenced by workplace intervention (Waddell and Burton, 2006). Because jobs and careers contribute quite a bit to worker wellbeing as a whole, employers assume a critical role in helping employees build healthy behaviours into their lives. The purposes of this paper are to: 1) develop holistic aspects of wellbeing, including theoretical underpinnings; 2) explore workplace sources that contribute to holistic workplace wellbeing, but also un-wellbeing; 3) examine workplace wellbeing strategic sustainability consequences for the firm.